PENGENALAN MODEL JEMBATAN AKUNTABILITAS: SEBUAH KERANGKA EVALUASI PROGRAM UNTUK KONSELOR SEKOLAH - Wahyu Nanda Eka Saputra, author (JURNAL FOKUS KONSELING, 2015)
One of evaluation model counseling programs is accountability bridge model. In this model, counseling evaluation cycle is devided into two cycles. The first cycle is counseling program evaluation and the second is counseling context evaluation cycle. Counseling program evaluation cycle focus on the result of counseling service, while counseling context evaluation cycle focus on the trial of counseling service impact by stake holder and uses its feedback, the result of need assessment for fostering and repairing the goal of counseling program. Both cycle are connected by accountability bridge, which the result of counseling practice is communicated to stakeholder in context of the bigger service system.Keywords: Accountability Bridge Model, Program Evaluation, Context Evaluation